The Hitchhiker's guide to the galaxy. The quandry phase - Adams, Douglas, 1952-2001.; Jones, Simon, 1950-; McGivern, Geoffrey; Moore, Stephen, 1937-; Franklyn, William, 1926-2006; OverDrive, Inc. (2005)
Don't panic! The Hitchhiker's saga returns once again with a brand new full-cast dramatisation of "So long" and "Thanks for all the fish," the fourth book in Douglas Adams's famous "trilogy in five parts." The Earth has miraculously reappeared and, even more miraculously, Arthur Dent has found it. Returning to his cottage after -- well -- ages, he falls in love with the girl of his dreams. But Ford Prefect is on to something which might well burst Arthur's bubble. There is, after all, something very fishy about his girlfriend's feet, and what has happened to all the dolphins? Perhaps, at last, all will be revealed in God's last message to His creation ... Simon Jones returns as Arthur, Geoffrey McGivern as Ford and Stephen Moore as Marvin. William Franklyn is the Book, and there is a whole host of famous guest stars.
Downloadable audio file.
Title from: Title details screen.
Unabridged.
Duration: 2:23:46.
Based upon the book The hitch-hiker's guide to the galaxy by Douglas Adams.
Special features: 30 minutes of material not heard on BBC Radio 4.
Keywords: Dent, Arthur -- (Fictitious character) -- Drama; Prefect, Ford -- Drama; Interstellar travel -- Drama; Radio adaptations; Radio plays; Science fiction radio programs; Downloadable audio books